Effects of whole-grain rye porridge with added inulin and wheat gluten on appetite, gut fermentation and postprandial glucose metabolism: a randomised, cross-over, breakfast study. Issue 12 (10th January 2017) - Lee, Isabella; Shi, Lin; Webb, Dominic-Luc; Hellström, Per M.; Risérus, Ulf; Landberg, Rikard
Abstract: Whole-grain rye foods reduce appetite, insulin and sometimes glucose responses. Increased gut fermentation and plant protein may mediate the effect. The aims of the present study were to investigate whether the appetite-suppressing effects of whole-grain rye porridge could be enhanced by replacing part of the rye with fermented dietary fibre and plant protein, and to explore the role of gut fermentation on appetite and metabolic responses over 8 h. We conducted a randomised, cross-over study using two rye porridges (40 and 55 g), three 40-g rye porridges with addition of inulin:gluten (9:3; 6:6; 3:9 g) and a refined wheat bread control (55 g), served as part of complete breakfasts. A standardised lunch and an ad libitum dinner were served 4 and 8 h later, respectively. Appetite, breath hydrogen and methane, glucose, insulin and glucagon-like peptide-1 (GLP-1) responses were measured over 8 h. Twenty-one healthy men and women, aged 23–60 years, with BMI of 21–33 kg/m 2 participated in this study. Before lunch, the 55-g rye porridges lowered hunger by 20 % and desire to eat by 22 % and increased fullness by 29 % compared with wheat bread ( P <0·05). Breath hydrogen increased proportionally to dietary fibre content ( P <0·05). Plasma glucose after lunch was 6 % lower after the 55-g rye porridges compared with wheat bread ( P <0·05) and correlated to breath hydrogen ( P <0·001). No differences were observed in ad libitum food intake, insulin or GLP-1. We conclude that no further increase in satiety was observed when replacing part of the rye with inulin and gluten compared with plain rye porridges.